Islamic principles of administration: implications on practices in organization - Salleh, Mohamad Johdi (2012)
The purpose of this paper is to develop a discussion expounding the principles of Islamic administration and its implication to practices in any organization. The paper will enumerate basic principles of Islamic administration that are extracted from the primary and secondary sources of shariah, its definition and scope, application and implementation and more significantly; its impact to the practice in any organization. The paper will also highlight the relationship of Islamic principles of administration vis-à-vis the mainstream corporate values and good governance as adopted by world leading firms and organization particularly in amplifying the impact of those principles to the aforesaid firms and organization in a real sense. The discussion of the paper in relation to the impact of the Islamic principles of administration would centre around the three main areas of any organization i.e. employment practices, managerial practices and lastly the training and development. At the climax of the discussion, readers of the paper will find that Islamic principles of administration do not merely serve as a concept or theoretical aspect in the Islamic administration but rather as a very practical tool in serving the needs of any organization in facing the challenges of this new globalization era.